Zarządzanie produktami bankowymi - Swat, Bogumiła (Managing of the Banking Products, 2005)
The quality of the banking products is a relevant area of competition in the financial market. Creating the competitive edge exceeds identifying the quality and kinds of products offered. It concerns more and more the procedures of the process of formulating the offer, the choice of financial model and the organization of the operational process of function and support.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 216-229